Recent Developments in the Law of Equitable Remedies: What Canada Can Do For You - Berryman, Jeff (Victoria University of Wellington Law Review, 2002)
The Supreme Court of Canada has clearly enunciated a distinct equity jurisprudence for Canada. This paper discusses certain aspects of the most recent developments particularly in the area of equitable remedies. The recent "explosion" in the use of Anton Piller decisions is charted, and where appropriate, analogous Commonwealth decisions are discussed. The use of Injunctive remedies is canvassed, as well as specific performance.